2015
DOI: 10.1016/j.jadohealth.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impacts of an Intimate Partner Violence Prevention Program Based on Child Marriage Status in Rural Côte d'Ivoire

Abstract: Purpose Little is known about whether effectiveness of intimate partner violence prevention programming varies for women who were married as child brides, given their additional social vulnerabilities. This subanalysis sought to assess treatment heterogeneity based on child marriage status for an intervention seeking to reduce intimate partner violence. Methods A randomized controlled trial assessing the incremental effectiveness of gender dialogue groups in addition to group savings on changing past-year in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 28 publications
3
28
1
2
Order By: Relevance
“…This may be because the policy helped delay marriage, and was effective at preventing IPV among girls who delayed marriage but not for the subsample who continued to marry early. This is consistent with other research including a recent study from Cote D'Ivoire which found community based gender dialogue groups and IPV prevention programming were ineffective at decreasing physical or sexual violence experienced among women married as child brides, despite these interventions having positive effects on non-child brides [47].…”
Section: Viewpoints Research Theme 3: Gender Norms and Healthsupporting
confidence: 91%
“…This may be because the policy helped delay marriage, and was effective at preventing IPV among girls who delayed marriage but not for the subsample who continued to marry early. This is consistent with other research including a recent study from Cote D'Ivoire which found community based gender dialogue groups and IPV prevention programming were ineffective at decreasing physical or sexual violence experienced among women married as child brides, despite these interventions having positive effects on non-child brides [47].…”
Section: Viewpoints Research Theme 3: Gender Norms and Healthsupporting
confidence: 91%
“…These findings suggest that the dynamics of being married not only interfere with girls' access to education and expose them to a greater likelihood of experiencing violence, but being married makes the potential protective role of education vis-à-vis violence less pronounced. These findings are supported by existing research documenting the ways in which child marriage can potentially moderateand thereby diminish the effect of -supportive interventions for married girls (Falb et al, 2015. ) This study also highlights an association between girls who were married, and lower levels of participation in formal education.…”
Section: Discussionsupporting
confidence: 68%
“…Child marriage can be linked to a range of poor social and health outcomes for women and girls, including high risks of early pregnancy [13], mental health issues due to forced early sexual debut [14], and maternal death and disability, including postpregnancy complications [15]. Additional sexual health challenges, such as the lack of agency of brides to negotiate the use of condoms even in conditions of high risk of HIV infection, are reported [16]. Such challenges are associated with the potential presence of increasing risk of domestic violence and power differentials in the relationship, which could be attributed to differences in age.…”
Section: Introductionmentioning
confidence: 99%
“…Such challenges are associated with the potential presence of increasing risk of domestic violence and power differentials in the relationship, which could be attributed to differences in age. There is evidence which shows that early marriage is linked to negative social outcomes, including school dropout, lack of employment and low educational attainment [15,16].…”
Section: Introductionmentioning
confidence: 99%